INSERTION COMMERCIAL SECTOR AND COMPETITIVENESS IN ARGENTINA: AN ANALYSIS ABOUT THE POSSIBILITY OF DEINDUSTRIALIZATION OF ECONOMICS - Michael Gongalves da Silva; Clesio Lourenço Xavier; Vanessa Siqueira Peres da Silva (Cadernos Prolam/USP, 2013)
Due to high global demand for goods intensive in natural resources, in recent years, this article aimed to measure, through the analysis of the trade balance, as Argentina’s economy, between the years 2000-2011. Using the sectoral aggregation proposed by the Organisation for Economic Co-Operation and Development (OECD), classification of technological intensity, it was established that the Argentine economy growing trade balances obtained for the sectors producing non industrial goods, and growing trade deficits with the other sectors of the economy. These results may point to a possible de